Social inclusion of street vendors in Harare: Challenges and opportunities - Chibango, Conrad (HTS teologiese studies, 2024)
Zimbabwe’s unending socioeconomic crisis has led to the flooding of informal street vendors in its urban areas, a development that has led to incessant clashes between the street vendors and the local authorities. Literature has shown that street vending is a global phenomenon and its problems could be addressed through best practices of inclusivity. This study examined the situation of informal street vendors in Harare in the light of social inclusion. It also made use of insights from Pope Francis regarding World Popular Movements. Data were collected through focus group discussions comprising six informal street vendors operating in Harare as its participants. Findings revealed that informal street vendors in Harare faced many structural challenges, one of which included operating in contested spaces characterised by violent evictions from vending sites, bribery and power struggles. Results also showed that street vendors lacked access to bank loans, information, and even the power to influence policies which directly affected them. Based on these findings, it was argued that the informal street vendors were socially excluded and needed to be integrated into the economic fabric of the urban society. This social inclusion process was considered as only possible if local authorities adopted an inclusive approach to policymaking. This would entail involving the street vendors when crafting policies that directly affect them. It was recommended that Harare City Council regularises street vending, aligns its by-laws to the National Constitution, and that it also formulates inclusive policies.Contribution: The article makes a contribution towards the promotion of an inclusive society whereby everyone has equal access to social and economic opportunities.